Biogeochemical cycling in the Bering Sea over the onset of major Northern Hemisphere glaciation - Swann, George E.A.; Snelling, Andrea M.; Pike, Jennifer (American Geophysical Union, 2016)
The Bering Sea is one of the most biologically productive regions in the marine system and plays a key role in regulating the flow of waters to the Arctic Ocean and into the subarctic North Pacific Ocean. Cores from IODP Expedition 323 to the Bering Sea provide the first opportunity to obtain reconstructions from the region that extend back to the Pliocene. Previous research at Bowers Ridge, south Bering Sea, has revealed stable levels of siliceous productivity over the onset of major Northern Hemisphere Glaciation (NHG) (c. 2.85-2.73 Ma). However, diatom silica isotope records of oxygen (δ18Odiatom) and silicon (δ30Sidiatom) presented here demonstrate that this interval was associated with a progressive increase in the supply of silicic acid to the region, superimposed on shift to a more dynamic environment characterized by colder temperatures and increased sea ice. This concluded at 2.58 Ma with a sharp increase in diatom productivity, further increases in photic zone nutrient availability and a permanent shift to colder sea surface conditions. These transitions are suggested to reflect a gradually more intense nutrient leakage from the subarctic northwest Pacific Ocean, with increases in productivity further aided by increased sea-ice and wind-driven mixing in the Bering Sea. In suggesting a linkage in biogeochemical cycling between the south Bering Sea and subarctic Northwest Pacific Ocean, mainly via the Kamchatka Strait, this work highlights the need to consider the inter-connectivity of these two systems when future reconstructions are carried out in the region.